2004
DOI: 10.1097/01.prs.0000111591.62685.f8
|View full text |Cite
|
Sign up to set email alerts
|

Practice Advisory on Liposuction

Abstract: COMMITTEE STATEMENT: At the 69th annual meeting of the American Society of Plastic Surgeons (ASPS) in October of 2000, the ASPS Board of Directors convened the Task Force on Patient Safety in Office-Based Surgery Facilities. The task force was assembled in the wake of several highly publicized patient deaths involving plastic surgery and increasing state legislative and regulatory activity of office-based surgery facilities. In response to the increased scrutiny of the office-based surgery setting, the task fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(74 citation statements)
references
References 52 publications
0
69
0
Order By: Relevance
“…However, several studies attempted to measure the specific body image issues related to adolescents seeking cosmetic surgery. The previously cited study of Dutch adolescents (ages [12][13][14][15][16][17][18][19][20][21][22] presenting for plastic surgery found that these patients did not differ from other adolescents on most selfconfidence or mental health measures. However, they were slightly less confident of their physical appearance and romantic appeal, and significantly more dissatisfied with the body part for which they were considering surgery compared to adolescents in the general population [21].…”
Section: Mental Health and Cosmetic Surgerymentioning
confidence: 98%
See 1 more Smart Citation
“…However, several studies attempted to measure the specific body image issues related to adolescents seeking cosmetic surgery. The previously cited study of Dutch adolescents (ages [12][13][14][15][16][17][18][19][20][21][22] presenting for plastic surgery found that these patients did not differ from other adolescents on most selfconfidence or mental health measures. However, they were slightly less confident of their physical appearance and romantic appeal, and significantly more dissatisfied with the body part for which they were considering surgery compared to adolescents in the general population [21].…”
Section: Mental Health and Cosmetic Surgerymentioning
confidence: 98%
“…The different techniques (tumescent, superwet, and ultrasound-assisted liposuction) are associated with additional complications such as skin or deep tissue damage. The American Society of Plastic Surgeons' advisory states that the likelihood of serious medical complications, such as lidocaine toxicity and fluid accumulation in the lungs, increase with "the number of sites treated and the volume of fat aspirated" [16].…”
Section: Liposuctionmentioning
confidence: 99%
“…Major com- plications include bleeding, infection, skin necrosis, vital organ injury, adverse anesthesia reaction, pulmonary embolism, and fat embolism. 1 A census survey of North American cosmetic surgeons in the mid-1990s revealed a perioperative mortality rate of 20 per 100,000 cases; death was attributed to pulmonary embolism in 23% of the fatal cases and fat embolism was identified as the cause of death in 8.5% of cases. 2 Fat embolism occurs when adipocytes and small blood vessels are damaged during the procedure, introducing lipid microthrombi into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Liposuction remains one of the procedures most commonly performed by plastic surgeons and is predominantly performed for aesthetic reasons, 5 gaining attention in the public eye only if a tragic death occurs 6,7 or presented on television purely for entertainment and noneducational purposes. Recent data highlighted in this review show that there may be physiologic improvements following liposuction that could not only help the self-esteem of individuals who have supersized themselves but also result in unanticipated improvements to their long-term health.…”
mentioning
confidence: 99%